2024
DOI: 10.1186/s12909-023-04918-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting students’ academic progress and related attributes in first-year medical students: an analysis with artificial neural networks and Naïve Bayes

Diego Monteverde-Suárez,
Patricia González-Flores,
Roberto Santos-Solórzano
et al.

Abstract: Background Dropout and poor academic performance are persistent problems in medical schools in emerging economies. Identifying at-risk students early and knowing the factors that contribute to their success would be useful for designing educational interventions. Educational Data Mining (EDM) methods can identify students at risk of poor academic progress and dropping out. The main goal of this study was to use machine learning models, Artificial Neural Networks (ANN) and Naïve Bayes (NB), to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Comparing the performance of our prediction models with those of other studies presents challenges, since in our research, the target variable-self-reported academic performance (ACAD_PERFO)-is subjective, while in most of the others, the target variable is an objective measure like GPA or equivalent ratings [28,[77][78][79][80][81][82][83][84][85][86][87][88][89][90]. We were interested in how students perceived their performance, which is totally different from actual academic achievements.…”
Section: Models Metrics and Comparisonmentioning
confidence: 99%
“…Comparing the performance of our prediction models with those of other studies presents challenges, since in our research, the target variable-self-reported academic performance (ACAD_PERFO)-is subjective, while in most of the others, the target variable is an objective measure like GPA or equivalent ratings [28,[77][78][79][80][81][82][83][84][85][86][87][88][89][90]. We were interested in how students perceived their performance, which is totally different from actual academic achievements.…”
Section: Models Metrics and Comparisonmentioning
confidence: 99%